The big why of implementing computational thinking in STEM education: a systematic literature review - Abdul Wahab, Norhafizan; Talib, Othman; Razali, Fazilah; Kamarudin, Nurzatulshima (Secholian Publication, 2021)
Computational Thinking (CT) has been increasingly embraced as a reformation in STEM education. This paper discusses why the implementation of CT would have a considerable effect on STEM education. The first objective of this systematic literature review is to identify the subjects that incorporate the most elements of CT in STEM education. Secondly, it aims to provide an overview of CT practices in the classrooms. Finally, the major findings of this study seek to discuss the benefits and challenges of the use of CT in STEM education. Fifteen articles were methodically selected from Scopus, Web of Science, Dimensions, and Google Scholar databases as the relevant studies to be discussed in this systematic study, based on the PRISMA Statement (Preferred Reporting Items for Systematic Reviews and Meta-Analysis) review technique. This review identifies current research gaps and directions for the practice and implementation of CT in STEM education. Further analysis of the articles has contributed to a conclusion that CT has become more widespread and multi-disciplinary and seems to have propagated improvements in STEM education. Still, a new study is required, especially on long-term implications.